Consider the system for $(x_1(t),x_2(t))$

\begin{align} \dot{x}_1 &= x_1^2+x_1^3+x_2\\ \dot{x}_2 &= x_1^2+u \end{align}

Find a function $u=\phi(x_1(t),x_2(t))$ so that if

$$V(x) = \frac12(x_1^2+(x_1+x_1^2+x_1^3+x_2)^2)$$

then $\dot{V}=-2V$.

So my method was to find $\dot V$ then equate that to $-2V$ and rearrange to find $u$. But this seems very messy, is there a nicer way to do this?

\begin{align} \dot{V} &= x_1\dot{x}_1 + (\dot x_1 + 2x_1\dot x_1 + 3x_1^2\dot x_1 + \dot x_2)(x_1+x_1^2+x_1^3+x_2) \\ &= \dot x_1\big[x_1 + (1 + 2x_1+3x_1^2)(x_1+x_1^2+x_1^3+x_2)\big] + \dot x_2(x_1+x_1^2+x_1^3+x_2) \\ &= (x_1^2+x_1^3+x_2)\big[x_1 + (1 + 2x_1+3x_1^2)(x_1+x_1^2+x_1^3+x_2)\big] + (x_1^2+u)(x_1+x_1^2+x_1^3+x_2) \\ &= (x_1^2+x_1^3+x_2)\big[x_1 + (1 + 2x_1+3x_1^2)(x_1+x_1^2+x_1^3+x_2)\big] + x_1^2(x_1+x_1^2+x_1^3+x_2) + u(x_1+x_1^2+x_1^3+x_2)\\ &=-(x_1^2+(x_1+x_1^2+x_1^3+x_2)^2) \end{align}

$$\iff u(x_1+x_1^2+x_1^3+x_2)=-(x_1^2+(x_1+x_1^2+x_1^3+x_2)^2)-x_1^2(x_1+x_1^2+x_1^3+x_2)-(x_1^2+x_1^3+x_2)\big[x_1 + (1 + 2x_1+3x_1^2)(x_1+x_1^2+x_1^3+x_2)\big]$$

$$\implies u=-\frac{(x_1^2+(x_1+x_1^2+x_1^3+x_2)^2)}{(x_1+x_1^2+x_1^3+x_2)}-x_1^2-(x_1^2+x_1^3+x_2)\left[\frac{x_1}{(x_1+x_1^2+x_1^3+x_2)} + (1 + 2x_1+3x_1^2)\right]$$

  • $\begingroup$ It doesn't seem possible to use any other approach. I am curious why would anyone want to do what you ask. $\endgroup$ – John B Apr 29 '16 at 18:32

This is clearly an example of backstepping design. This is a sequential design methodology for strict feedback nonlinear systems (note that in your example $x_2$ can be seen as an 'input' to the $x_1$ subsystem). So the idea is to select an appropriate virtual control $\alpha_1(x_1)$ that can stabilize the $x_1$ subsystem if $x_2=\alpha_1(x_1)$ and then drive the difference $z_2:=x_2-\alpha_1(x_1)$ to zero by selecting suitable $u$.

So if you select $$\alpha_1(x_1)=-x_1^2-x_1^3-x_1$$ and define the new error variable $$z_2:=x_2-\alpha_1(x_1)=x_1+x_1^2+x_1^3+x_2$$ then your $V$ takes the form $$V=\frac{1}{2}x_1^2+\frac{1}{2}z_2^2$$ and $$\dot{x}_1=-x_1+z_2\\ \dot{z}_2=x_1^2+u-\frac{d\alpha_1}{dx_1}\dot{x}_1$$ Note now that $$\dot{V}=x_1(-x_1+z_2)+z_2\dot{z}_2=-x_1^2+z_2(x_1+x_1^2+u-\frac{d\alpha_1}{dx_1}\dot{x}_1)$$ Thus selecting $$u=-x_1-x_1^2+\frac{d\alpha_1}{dx_1}\dot{x}_1-z_2$$ guarantees $$\dot{V}=-x_1^2-z_2^2=-2V$$ Hence the desired control input is $$u=-x_1-x_1^2+(-1-2x_1-3x_1^2)(x_1^2+x_1^3+x_2)-(x_2+x_1+x_1^2+x_1^3)$$

  • $\begingroup$ It would be interesting to know why my answer was downvoted. $\endgroup$ – RTJ Apr 29 '16 at 22:23

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.